Kemampuan Mahasiswa Pendidikan Bahasa Indonesia FKIP Universitas Syiah Kuala Memahami Kosakata Dan Istilah Yang Berhubungan Dengan Merebaknya Virus Corona Tahun 2019 - Octavia, Yola; Armia, Armia; Iqbal, Muhammad (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
This research is entitled "The Ability of Indonesian Language Education Students FKIP Universitas Syiah Kuala to Understand Vocabulary and Terms Related to the Corona Virus Outbreak in 2019". The purpose of this study was to find out how the level of ability of Indonesian Language Education students at FKIP Universitas Syiah Kuala to understand vocabulary and terms related to the outbreak of the Coronavirus in 2019. The research approach used in this study was a descriptive quantitative approach.Â  The population in this study were students of Indonesian Language Education FKIP Universitas Syiah Kuala class 2016 to 2020 with a total of 418 students, and the sample in this study amounted to 41 students taken 10% of the total population.Â  The data collection technique in this study is a test technique. The results showed that the students' ability of Indonesian Language Education FKIP Universitas Syiah Kuala to understand vocabulary and terms related to the outbreak of the Coronavirus in 2019 scored 65. The highest score achieved by students was 92,4 and the lowest score achieved by students was 23,1. Then the results of the percentage of students who were in the very good category were 1 person or about 2,43%, then students who were included in the good category amounted to 16 people or around 39,02%, then 18 people who were in the moderate category or around 43, 90%, for students who were in the poor category were 3 people or about 7,31%, and students who were included in the very poor category were 3 people or about 7,31%. Based on the results of the research, the ability of Indonesian Language Education students at FKIP Universitas Syiah Kuala to understand vocabulary and terms related to the outbreak of the Coronavirus in 2019 is included in the sufficient category with an average score of 65 which is in the 56-70 value range.